Effect of dietary supplementation with vitamin C on the productive performance, stress and immune response of turkey reared in a natural hypoxic environment - Paredes, Manuel (2020)
This research aimed to evaluate the effect of the addition of vitamin C in the diet of turkeys reared in a natural hypoxic environment (high Andean zone of Peru, 2750 masl), on productive performance, hematological values, stress status and immune function. One-day-old Hybrid Converter turkeys were assigned to 5 groups of 5 replicates. The birds of the 5 groups were fed a basal diet supplemented with 0 (control group), 500, 1000, 1500 and 2000 mg/kg of vitamin C for 91 days. Vitamin C decreased heterophile / lymphocyte levels (p < 0.05). Compared to the control group, vitamin C at a level greater than or equal to 1000 mg / kg decreased bird mortality (p < 0.05), reduced the stress indicator (p < 0.05), increased the antibody titer (p < 0.05), but did not improve growth parameters (p > 0.05). Consequently, dietary supplementation with vitamin C could regulate productive performance, by reducing the level of mortality, promoting immune function, and improving the state of stress in commercial turkeys, reared in a natural hypoxic environment. These results encourage commercial turkey meat production in hypoxic areas.